Verbal autopsy: reliability and validity estimates for causes of death in the Golestan Cohort Study in Iran. - Hooman Khademi; Arash Etemadi; Farin Kamangar; Mehdi Nouraie; Ramin Shakeri; Behrooz Abaie; Akram Pourshams; Mohammad Bagheri; Afshin Hooshyar; Farhad Islami; Christian C Abnet; Paul Pharoah; et al. (PLoS ONE)
Background Verbal autopsy (VA) is one method to obtain valid estimates of causes of death in the absence of valid medical records. We tested the reliability and validity of a VA questionnaire developed for a cohort study in Golestan Province in northeastern Iran. Method A modified version of the WHO adult verbal autopsy was used to assess the cause of death in the first 219 Golestan Cohort Study (GCS) subjects who died. The GCS cause of death was determined by two internists who independently reviewed all available medical records. Two other internists ("reviewers") independently reviewed only the VA answers and classified the cause of death into one of nine general categories; they repeated this evaluation one month later. The reliability of the VA was measured by calculating intra-reviewer and inter-reviewer kappa statistics. The validity of the VA was measured using the GCS cause of death as the gold standard. Results VA showed both good validity (sensitivity, specificity, PPV, and NPV all above 0.81) and reliability (kappa>0.75) in determining the general cause of death independent of sex and place of residence. The overall multi-rater agreement across four reviews was 0.84 (95%CI: 0.78-0.89). The results for identifying specific cancer deaths were also promising, especially for upper GI cancers (kappa = 0.95). The multi-rater agreement in cancer subgroup was 0.93 (95%CI: 0.85-0.99). Conclusions VA seems to have good reliability and validity for determining the cause of death in a large-scale adult follow up study in a predominantly rural area of a middle-income country.